Dimensionamento otimizado de vigas alveolares de aço - Lubke, Gabriela Pereira (2017)
Open web-expanded steel beams are structural elements achieved by cutting the web of the root beam in a certain pattern and then welding two parts each other. As a result of these processes the overall beam depth increases which in return causes increase in the capacity of the original section. The openings, together with the addition of useful profile height, make this type of beam susceptible to new ways of collapse, and increases existing failure modes. This paper proposes a formulation for the design of cellular beams steel optimally using the formulations developed by Cimadevilla (2000), Abreu (2011), Silveira (2011) and Veríssimo et al. (2012), takinginto account the geometry of restrictions set by Oliveira (2012). The validation of the computer program developed for the accomplishment of results with results obtained through manually solved examples as the basis of a descriptive formulation by Veríssimo et al. (2012), as the Brazilian standard does not define the design parameters for this type of profile. The program was developed in the Matlab platform, and for a solution of the optimization problems were used in internal Matlab algorithms, such as interior points, quadratic programming and genetic algorithms. Initial examples point out that the sizing can be improved and no case of profiling a new cut line can be defined.